PENGELOLAAN DAS DENGAN PENDEKATAN EKOSISTEM: STUDI KASUS ANALISIS DEBIT SUNGAI BONE DAN BOLANGO DI KABUPATEN BONE BOLANGE, PROPINSI GORONTALO - Tresnadi, Hidir (Jurnal Hidrosfir Indonesia, 2008)
Water resources should be managed integratively in the term of forestry, agriculture, social economy, conservation and civilian. Bone-Bolango Regency, in the center, eastern and western part, passed by Bone dan Bolango Rivers. The upstream area of Bone and Bolango Rivers is Nani Wartabone national conservation forest. The watershed of Bone and Bolango Rivers are located among Bone Bolango, Gorontalo, Limboto, and Gorontalo Major region in the Gorontalo Province, meanwhile in thelarger system, they have share watershed to the North Sulawesi Province.Until now the watershed of Bone-Boelango is managed by Balai Pengelolaan DAS Boen Bolango, whereas groundwater resources develepment managed by P2AT, and local stakeholders such as Dinas Kimpraswil Tingkat I Propinsi Gorontalo and Dinas Kimpraswil Pemda Tingkat II Kabupaten Bone Bolango. The analysis of the annual debit of Bone and Bolango Rivers show that the trend of the average debit ratio to theminimum debit of the same year show gradually higher than dan before because of the deforestration of Bone and Bolango Rivers in the upstream of the rivers. So we have to manage the DAS of Bone and Bolango Rivers by the ecosistem approach to improve the deterioration of the the rivers.